PEMBATALAN PUTUSAN PENGADILAN NIAGA PADA PENGADILAN NEGERI JAKARTA PUSAT OLEH MAHKAMAH AGUNG TERKAIT DENGAN PUTUSAN PAILIT PT. DIRGANTARA INDONESIA - Sudana, I Wayan; Suardana, I Wayan (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 11, November 2013, 2013)
Injunction Cancellation transactions in central Jakarta district court supreme court decision related to bancrupty of PT. Dirgantara Indonesia Aerospace is to determine wheter revocation of the court injunction business center Jakarta state supreme court decision related to the bancrupty of PT. Dirgnatara Indonesia accordance with statutory provision which accurs. Methods of this journal are wearing writing method normative juridical law. Coclusion of this paper that deals cancellation injunction in central Jakarta district court supreme court decision related to the bancrupty of PT. Dirgantara Indonesia is not in accordance to the laws and regulations that occur because not filed by the Chancellor of the Exchequer republic Indonesia.
Keywords: Cancellation, Injunction,Bankruptcy, Supreme Court.